College Students' Ability in Using Prepositions "in, on, at" at Politeknik Kesehatan YRSU Dr.Rusdi Medan in 2022 - Siregar, Sri Handayani (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2025)
This research deals with the college students’ ability in using preposition “in, on, at”. It attempts to find out how far the college students understand about these prepositions. The population of this research was 2022/2023 of semester I Physiotherapy students of Politeknik Kesehatan YRSU Dr. Rusdi Medan. The total number of populations were 50 Physiotherapy college students. To obtain the data, a set of multiple choice was administered to the total sample. After analyzing the data, it was found that the Physiotherapy college students were able to use prepositions “in, on, at”. There were 36 Physiotherapy college students or 75% of the sample who were able to do the test and 14 Physiotherapy college students or 25% of the sample who were unable. Finally, the semester I Physiotherapy college students of Politeknik Kesehatan YRSU Dr.Rusdi Medan were able in using preposition “in, on, at”.